Concise Guide to Computation Theory - Maruoka, Akira (Springer Nature, 2011)
Combining lucid description and illustrations with rigorous arguments and detailed proofs, this book examines the core concepts of automata and languages, computability, and complexity of computation, and offers a solid foundation in computation theory.